Powerless security for Cardiac Implantable Medical Devices: Use of Wireless Identification and Sensing Platform. (1st April 2018) - Ellouze, Nourhene; Rekhis, Slim; Boudriga, Noureddine; Allouche, Mohamed
Abstract: Implantable Medical Devices are therapeutic devices designed to be surgically implanted into the body of a patient to continuously monitor his/her physiological parameters and automatically execute the suitable therapeutic functions when a chronic disorder is detected. Because of their therapeutic and life-saving benefits, cardiac IMDs, such as Pacemakers and Cardiac Defibrillators, are increasingly being used by patients to treat cardiac arrhythmia. Using an external programmer, cardiac IMDs are wirelessly configured and diagnosed by healthcare professionals. Nevertheless, the use of wireless networks to remotely access to these medical devices has shown important security concerns. In particular, it has been stated that lethal attacks can be launched on these devices. In this paper, we propose a powerless security solution to protect cardiac IMDs against security threats. We firstly identify and classify the main security attacks threatening IMDs, then we extend the IMD architecture by introducing a Radio Frequency Identification (RFID) system. Thanks to the use of a Radio Frequency energy harvesting solution, we design a powerless mutual authentication protocol between the IMD and the programmer allowing the prevention against battery depletion attacks. We also implement a technique for the dynamic biometric keys extraction from electrocardiogram signals collected at both sides (the programmer and the IMD), allowing a secure generation and distribution of master keys between the IMD and the programmer. A discussion about the main properties offered by the proposed solution and a simulation is conducted to evaluate its efficiency in protecting cardiac IMDs.